Analisis Diversifikasi Portofoli Investasi Internasional Terhadap Risiko Dan Return - Mutiara Hayandani; Pina Aulia Maharani; Sintia Anggraeni; Perwito Perwito (Indo Publishing, 2026)
This study was conducted to find out the benefits of diversifying global investment portfolios in terms of risk and return by utilizing the IHSG, S&P 500, Nikkei, and FTSE 100 stock indices. The methodology applied includes descriptive statistical analysis of returns and risks, as well as a study of the correlation between indices illustrated through correlation mapping. The findings of this study indicate that the Nikkei offers the highest average returns and has the highest risk, while the S&P 500 shows the lowest average returns with the lowest level of risk. The IHSG and FTSE 100 are in the moderate returns and risk category. Correlation analysis shows that the relationship between indices tends to be weak, indicating that integration in the global stock market has not yet been fully realized. These results confirm that portfolio diversification at the international level can provide benefits in reducing investment risk without significantly sacrificing potential returns.